Comprehensive transcriptomic analysis revealing the regulatory dynamics and networks of the pituitary-testis axis in sheep across developmental stages - Li, Shanglai; Zhao, Bingru; Yang, Hua; Dai, Keke; Cai, Yu; Xu, Hui; Chen, Peiyong; Wang, Feng; Zhang, Yanli (Frontiers in Veterinary Science, 2024)
Spermatogenesis is a complex process intricately regulated by the hypothalamic-pituitary-testis (HPT) axis. However, research on the regulatory factors governing the HPT axis remains limited. This study addresses this gap by conducting a comprehensive analysis of transcriptomes from the pituitary and testis tissues across various developmental stages, encompassing embryonic day (E120), neonatal period (P0), pre-puberty (P90), and post-puberty day (P270). Utilizing edgeR and WGCNA, we identified stage-specific genes in both the pituitary and testis throughout the four developmental stages. Notably, 380, 242, 34, and 479 stage-specific genes were identified in the pituitary, while 886, 297, 201, and 3,678 genes were identified in the testis. Subsequent analyses unveiled associations between these stage-specific genes and crucial pathways such as the cAMP signaling pathway, GnRH secretion, and male gamete generation. Furthermore, leveraging single-cell data from the pituitary and testis, we identified some signaling pathways involving BMP, HGF, IGF, and TGF-β, highlighting mutual regulation between the pituitary and testis at different developmental stages. This study sheds light on the pivotal role of the pituitary-testis axis in the reproductive process of sheep across four distinct developmental stages. Additionally, it delves into the intricate regulatory networks governing reproduction, offering novel insights into the dynamics of the pituitary-testis axis within the reproductive system.